Strategies to Enlarge the Market Availability of Green Building Materials (GBM) for Construction Works: Gathering the “Low-Hanging Fruits” - Ismail, Nur Adlina; Khalil, Natasha; Abdullah Sani, Suwaibatul Islamiah; Husin, Husrul Nizam (Research in Management of Technology and Business, 2023)
One of the strategy to reduce environmental issues in construction is by having more green buildings. Among the approach towards green building criteria is through the green materials adoption. It starts with proper selection of green building materials (GBM) that has sustainable characteristics compared to conventional building materials. However, the applicability of GBM is still low and not a favoritism option towards greening the building. Among the contributed factor is due to its higher initial cost and lack of local construction products that are certified as eco-label by MyHIJAU directory. Therefore, this paper aims to identify the significant strategies towards promoting the GBM as the key catalyst to enlarge the market in construction, or the “low-hanging fruits” strategies. Questionnaire survey was disseminated to 205 respondents comprises of industry practitioners that involved in green building projects. 160 respondents has answered the survey and results revealed that there are eight (8) “low-hanging fruit” strategies that can used to enlarge the market availability for GBM. The top strategies are adopting green procurement, implement more green trainings and harmonise the information on cost and benefits of GBM. The findings able to assist the stakeholders, construction enablers, practitioners and policy makers in developing practical strategies towards enlarging the market availability of GBM in construction works.